DIGITAL LEADERSHIP SEBAGAI STRATEGI PENGEMBANGAN KOMPETENSI DIGITAL WIDYAISWARA DALAM ERA PEMBELAJARAN DIGITAL DI BPSDM KEMENTERIAN DALAM NEGERI, PPSDM REGIONAL BANDUNG DAN PPSDM REGIONAL YOGYAKARTA TAHUN 2023 - Kartiwi , Kartiwi (Bajang Institute, 2025)
The urgency of digital leadership for the strategy of developing the competence of instructors (widyaiswara) accelerates the quality of education for training participants. Digital leaders must possess a digital skillset, skilled in operationalizing digital learning, and a digital mindset, formulating a conceptual digital vision, and realizing it through digital implementation. This study analyzes digital leadership as a strategy for developing the competence of instructors (widyaiswara) in digital-based learning at the Ministry of Home Affairs' Human Resources Development Agency (BPSDM) and Regional Human Resources Development Centers (PPSDM) in 2023. Through qualitative descriptive research methods, this study found that digital leadership as a strategy for developing Widyaiswara's digital competence in the digital learning era improves Widyaiswara's competence in three main dimensions, namely digital mindset, digital skillset, and digital implementation. Widyaiswara's digital competence development strategy has obstacles in building a digital mindset, but there is intrinsic motivation from Widyaiswara to continue learning, continuous learning, competitiveness and relevance of the latest teaching materials, with a tendency to utilize new digital technologies in blended learning.The strategy for developing the digital skillset competency of the instructor is carried out through the instructor's skills in using digital technology, followed by the ability of the instructor to manage creative and innovative learning through the use of digital devices. The dimensions of the Digital Implementation competency development strategy for the instructor do not conflict with the principles of instructor competency which include learning management competency, personality competency, social competency and substantial competency and will only be realized when there is synergy between the instructor, training participants and organizers in this case PPSDM